Pre‐Zika descriptive epidemiology of microcephaly in Texas, 2008–2012. Issue 5 (24th November 2017) - Hoyt, Adrienne T.; Canfield, Mark A.; Langlois, Peter H.; Waller, Dorothy K.; Agopian, A. J.; Shumate, Charles J.; Hall, Noemi B.; Marengo, Lisa K.; Ethen, Mary K.; Scheuerle, Angela E.
Abstract: Background: There are limited population‐based studies on microcephaly. We characterized the epidemiology of microcephaly in Texas during a 5‐year period (2008–2012), prior to the Zika epidemic in the Western hemisphere (2015). The associations of suspected risk factors were compared across four clearly defined case groups. Methods: Data from the Texas Birth Defects Registry were used to calculate the prevalence of congenital microcephaly and crude and adjusted prevalence ratios using Poisson regression. Twelve maternal and infant factors were assessed across case groups, which included total (explained + unexplained), explained (e.g., syndromic), unexplained, and severe unexplained microcephaly (head circumference <3 rd percentile). Results: The birth prevalence for total and total severe microcephaly were 14.7 and 4.8 per 10, 000 livebirths, respectively. For explained and unexplained cases, significantly elevated risks were noted for mothers who were older (35+), less educated (≤12 years), diabetic (pre‐pregnancy or gestational), or had a preterm delivery. Unlike explained cases, however, mothers who were non‐White or smoked had an increased risk for unexplained microcephaly. Furthermore, young maternal age (<20), multiparity, and higher BMI reduced the risk for unexplained microcephaly. For severe unexplained cases, the risk profile was similar to that for all unexplained cases—with the exception of null associations noted for diabetes and birth year. Conclusions: We found that risk patterns for microcephaly varied across case groupings. Risk factors included maternal race/ethnicity, age, and smoking during pregnancy. Among severe unexplained cases, notable positive associations were seen among mothers who were non‐Hispanic Black or less educated, while inverse associations were noted for obesity.